CHALLENGES OF DİGİTAL TRANSFORMATİON OF ENTERPRİSES (FEATURES AND PROBLEMS OF IMPLEMENTING ECONOMIC REFORMS IN AZERBAIJAN, 2025)
The purpose of the article is to determine the assessment of the level of digitalization of enterprises in Azerbaijan using extensive survey data. The purpose of the article is to identify opportunities related to the digital transformation process. The survey results examined the current state of digitalization in enterprises and various factors affecting their digital capabilities. The results of this study are crucial for understanding the economic impact of digitalization in Azerbaijan and developing effective policies that support the growth and competitiveness of SMEs in the digital era.Keywords: digital transformation, Azerbaijan, digitalization, survey, economic impact, digital skills, barriers, opportunities.